The Effectiveness of Argumentative Repetition in the Poetry Collection of Duraid bin Al-Samma (applied models) - Alswaeer, Ali Odeh; Jaber, Heba Mustafa (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to trace the features of argumentative repetition in the poetry of Duraid bin Al-Sammah, investigate them, and then explain, study, and analyze them, elucidating the effect of argumentation in repetition and its ideal goal of persuasion, understanding, and establishing the argument. The study aims to clarify the intended goal as a result of Duraid Ibn Al-Samma’s reliance on argumentative repetition in an optimal manner through extensive and careful research into his poetic material, until this type becomes a prominent stylistic feature in his poetry and a necessity that he cannot ignore to convince and understand the recipient. Methodology: The study relies on the inductive and analytical approach to examine the extent of the effect of repetition, as an argument, in conveying the message of the speech to the recipient, making them convinced of it, and submitting to it. Results: Duraid bin Al-Samma sought to intensify the presence of argumentative repetition in his poetry, and the study found that this color was widespread in the poet’s poetry. Techniques of argumentative repetition were achieved in his poetry, including repetition of the condition, repetition of the word, repetition of the sentence in both its nominal and verbal types, repetition of negation, repetition of the structure, repetition of the vocative, repetition of the letter, and repetition of the interrogative. These factors significantly contributed to achieving the goal of inciting the feelings of the recipients clearly and clearly. Conclusion: The study concludes that Duraid bin Al-Samma’s poetry was rich in various aspects of repetition that would elevate the level of the artistic work and achieve an element: emphasis and understanding for the recipient through the mobilization of a wide range of repetitive methods. The work grew and flourished, and the verses were linked and harmonized with each other in a clear way. It is never hidden from view. Argumentative repetition was the poet’s first means of achieving his ideal goal, and he succeeded in employing argumentative repetition in all its forms